The Soloist : A Lost Dream, An Unlikely Friendship, and the Redemptive Power of Music - Lopez, Steve (London Black Swan, 2008)
The true story of Nathaniel Ayers, a musician who becomes schizophrenic and homeless, and his friendship with Steve Lopez, the Los Angeles columnist who discovers and writes about him in the newspaper.
Keywords: Violinists -- California -- Biography. -- Nathaniel Anthony Ayers